PENGGUNAAN HOT SPOT ANALYSIS UNTUK MENENTUKAN KLASTER EKONOMI WILAYAH DI PROVINSI JAWA TENGAH - Andri Kurniawan; Any Lestari (JURNAL GEOGRAFI, 2020)
The dominance of certain economic structures tends to encourage the formation of spatial clusters. With changes and shifts in the regional economic structure, it will also have an impact on shifting regional economic clusters. The research carried out is aimed at achieving the goal of identifying regional economic clusters and their spatial dynamics using Hot Spot Analysis (Getis Ord Gi *) in Central Java Province. This research will be conducted using quantitative methods by utilizing secondary data. The time period used in this study is to compare conditions in 2010 with 2018. The two-year data is used to analyze the spatial dynamics of economic clusters in Central Java Province. The data used to determine economic clusters are data on GDP at constant prices and GDP at constant prices per capita of all regencies/cities. To analyze the spatial variations of economic clusters in regencies/cities in Central Java Province, Hot Spot Analysis (Getis Ord Gi *) is used which is included in the Geographic Information System (GIS) software. From the results of PDRB data processing regencies/cites Constant Price, in Central Java Province two Hot Spot clusters were formed, namely the Demak Regency cluster and the Semarang City cluster as the first Hot Spot cluster, and Cilacap and Banyumas Regencies as the second Hot Spot cluster. During its development, the Demak Regency-Semarang City cluster has expanded spatially with the addition of the Semarang and Kendal Regencies. On the other hand, the expansion of the cluster did not occur in the Cilacap-Banyumas cluster, but instead, there was a reduction in cluster strength. Furthermore, from the processing of Getis Ord Gi * for per capita income data, in this case, measured from the GDP per capita constant price in 2010, it shows that in Central Java Province not only Hot Spots are formed but also Cold Spots are formed. This illustrates that in Central Java Province there are still areas with per capita income that are still lagging behind other regions. A different condition occurred in 2018, where the Cold Spot has actually expanded and no Hot Spot is found anymore. This illustrates that areas that are relatively underdeveloped are actually experiencing an expansion, which was originally only from Banjarnegara Regency which expanded to Wonosobo Regency.